Rapid Detection of Methicillin Resistance in Coagulase-Negative Staphylococci with the VITEK 2 System - Horstkotte, Matthias A. (American Society for Microbiology, 2002)
The aim of the present study was to evaluate the accuracy of the new VITEK 2 system (bioMérieux, Marcy l' Etoile, France) for the detection of methicillin resistance in coagulase-negative staphylococci (CoNS) by using AST-P515 and AST-P523 test cards. Analyses of the VITEK 2 oxacillin MIC determination evaluated according to the actual breakpoint (≥0.5 μg/ml) of the National Committee for Clinical Laboratory Standards resulted in a high sensitivity of 99.2% but a moderate specificity of 80%. The newly included oxacillin resistance (OR) test of the VITEK 2 system displayed a high sensitivity and a high specificity of 97.5 and 98.7%, respectively. Concordance between the results of the mecA PCR and the VITEK 2 oxacillin MIC was observed for almost all Staphylococcus epidermidis strains, but the reduced specificity was attributable to higher oxacillin MICs for mecA-negative non-S. epidermidis strains, especially S. saprophyticus, S. lugdunensis, and S. cohnii. Evaluation of alternative oxacillin MIC breakpoints of 1, 2, or 4 μg/ml resulted in improved degrees of specificity of 84, 90.7, and 97.3%, respectively. Only minor changes occurred in the corresponding sensitivity values, which were 98.4, 97.5, and 97.5%, respectively. Methicillin resistance in CoNS was detected after 7 and 8 h in 91.1 and 93.5% of the mecA-positive strains, respectively, by the VITEK 2 OR test and in 86.3 and 89.5% of the mecA-positive strains, respectively, by VITEK 2 oxacillin MIC determination. After 7 and 8 h the VITEK 2 OR test classified 59.2 and 78.9% of the mecA-negative strains, respectively, as susceptible to oxacillin, whereas comparable values were obtained 2 h later by VITEK 2 oxacillin MIC determination. The results of our study encourage the use of the VITEK 2 system, which proved to be a highly reliable and rapid phenotypic method for the detection of methicillin resistance in CoNS.